Emerging RNA-Dependent RNA Polymerase Mutation in a Remdesivir-Treated B-cell Immunodeficient Patient With Protracted Coronavirus Disease 2019. (28th September 2020) - Martinot, Martin; Jary, Aude; Fafi-Kremer, Samira; Leducq, Valentin; Delagreverie, Heloise; Garnier, Marc; Pacanowski, Jérôme; Mékinian, Arsène; Pirenne, France; Tiberghien, Pierre; Calvez, Vincent; Humbrecht, Catherine; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a newly discovered virus for which remdesivir is the only antiviral available. We report the occurrence of a mutation in RdRP (D484Y) following treatment with remdesivir in a 76-year-old female with post-rituximab B-cell immunodeficiency and persistent SARS-CoV-2 viremia. A cure was achieved after supplementation with convalescent plasma.